Dispatcher-assisted resuscitation - EuReCa_Serbia 2014-2019 - Lazić, Aleksandra; Milic, Sasa; Fiser, Zoran (Journal Resuscitatio Balcanica, 2020)
ABSTRACTBackground:There are studies that indicate that dispatcher-guided CPR increases survival in Out-Of-Hospital cardiac arrest (OHCA). In this study, we observed the role of dispatcher lead CPR in OHCA and determined it’s influence on return of spontaneous circulation and survival.Method:Data was collected via the National OHCA Registry Serbia. Results:The collected results were obtained from 40/179 municipalities, 48.7% of the population in Serbia. In the period of 2014 – 2019. 6312 OHCA were registered. A witness was present in 3655/6312 (57,91%) patients. Witness-CPR was performed in 365/3655 (9,99%) events, dispatch CPR was applied in 197/365 (53,9%) cases. The calculated chance for the ROSC is 1,2 higher when the dispatcher was leading the CPR compared to caseswhere the witness-CPR was performed without dispatchers assistance (OR = 1,128; 95%CI = 0,685–1,913).Conclusion:In observed data of the National OHCA Registry Serbia, the results indicate that the outcome was insignificantly improved compared to ROSC and survival rate when dispatch-lead-CPR was performed. There is no specific dispatcher education program in Serbia and that fact should be investigate in purpose of further results and activities.
Keywords: bystander CPR , witnessed cardiac arrest, out-of-hospital cardiac arrest, Basic Life Support, ROSC, dispatched guided CPR,